The Use of Lexical Hedges in Spoken Language by Female and Male Students - Rosanti, Elfira Dwi; Jaelani, Alan (ENGLISH JOURNAL, 2016)
This study aims to describe lexical hedges used by female and male students in spoken language and to analyze lexical hedges used by female and male students in debate. The method used in this research is descriptive-qualitative method. By using the framework of hedges proposed by Namasaraev (1997), it is concluded that that there are differences between female and male respondents’ tendency in choosing word of lexical hedges. Female respondents tend to use more lexical hedges than male respondents. In this regard, female respondents most frequently use lexical hedges of fillers such as; hmm, uhh, you know in their utterances; while male respondents most frequently use lexical hedges of fillers such as; I think, uhh, hmm in their utterances. Female respondents have wide range variety in choosing words of lexical hedges while male respondents are not productive enough in choosing the words of lexical hedges. It is shown by the number of lexical hedges used in giving opinion in debate context.